Pancreas transplantation: indications, surgical technique, and clinical significance: Presaditev trebušne slinavke: indikacija, kirurška tehnika, klinični pomen - Hladnik, Gaja; Flis, Vojko (Acta Medico-Biotechnica, 2024)
Pancreas transplantation (PT) is a vital therapeutic option for patients with diabetes mellitus (DM)|, particularly those with end-stage renal disease (ESRD) or severe metabolic complications. Over the past several decades, advancements in surgical techniques, organ preservation and procurement methods, and immunosuppression therapies have significantly enhanced post-transplant patient survival, graft survival, and quality of life. The primary goals of PT are to achieve effective and stable glycemic control, often leading to insulin independence, improve the patient's quality of life, and reduce secondary complications associated with DM. PT encompasses a variety of procedures, including PT alone from a living donor, whole PT, pancreas with kidney transplantation, and pancreatic islet cell transplantation. PT is most commonly performed in conjunction with kidney transplantation for selected patients with DM and ESRD. Over the past decade, unadjusted patient survival rates have exceeded 96% at 1-year post-transplant and > 80% at 5 years.
Keywords: pancreas transplantation, diabetes mellitus, glycemic control, simultaneous pancreas-kidney transplantation